I︠A︡kornyi︠a︡ mi︠e︡sta na poluostrovi︠e︡ Kamchatki︠e︡ / Izdanīe Gidrograficheskago Departamenta Morskago Ministerstva vʺ 1883 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1883)
Relief shown by hachures. Depths shown by soundings and isolines.; Title translation: Anchorage places on the Kamchatka Peninsula / published by the Hydrographic Department of the Admiralty in 1883.; Maps: Plan ustʹi︠a︡ ri︠e︡ki Kamchatki, po opisi Kreĭsera "Afrika" 1882 g. -- Karta Kamchatskago mysa, po opisi Kreĭsera "Afrika" 1882 g." -- "Plan Petropoavlovskoĭ gavani, po opisi Kreĭsera "Afrika" 1882 goda.; "No. 293" -- bottom right margin Grayscale;